2021
DOI: 10.1002/ana.26217
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic Influence on Slow Wave Slope Renormalization During Sleep

Abstract: Objective: Slow waves are thought to mediate an overall reduction in synaptic strength during sleep. The specific contribution of the thalamus to this so-called synaptic renormalization is unknown. Thalamic stroke is associated with daytime sleepiness, along with changes to sleep electroencephalography and cognition, making it a unique "experiment of nature" to assess the relationship between sleep rhythms, synaptic renormalization, and daytime functions. Methods: Sleep was studied by polysomnography and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…In contrast to spindle density, neither slope55 nor the slow wave-spindle temporal coupling was predictive for later behavioral status. Although the slow wave slope is closely linked to synaptic strength and a reduction has been shown in pediatric patients with impaired synaptic plasticity (Gefferie et al, 2021) and after thalamic stroke (Jaramillo et al, 2021), our results provide no evidence for its suitability as an early biomarker for later behavioral status. This is the first study to report relationships between slow wave-spindle coupling and behavioral development in infants, yet the functional significance of this coupling remains to be established in future experiments that may include cognition and memory tasks.…”
contrasting
confidence: 63%
“…In contrast to spindle density, neither slope55 nor the slow wave-spindle temporal coupling was predictive for later behavioral status. Although the slow wave slope is closely linked to synaptic strength and a reduction has been shown in pediatric patients with impaired synaptic plasticity (Gefferie et al, 2021) and after thalamic stroke (Jaramillo et al, 2021), our results provide no evidence for its suitability as an early biomarker for later behavioral status. This is the first study to report relationships between slow wave-spindle coupling and behavioral development in infants, yet the functional significance of this coupling remains to be established in future experiments that may include cognition and memory tasks.…”
contrasting
confidence: 63%
“…Notably, projections from the central medial thalamus to the prefrontal cortex have been found to modulate parvalbumin cells in cortical layers 2/3, which are necessary for the consolidation of emo-tional memories during REM-sleep [97]. Although experimental findings suggest that the thalamus is involved in the regulation of REM sleep, no significant differences in REM sleep quantity have been observed in thalamic stroke patients [45,46,50,51]. The microarchitecture of REM sleep (e.g., saw-tooth waves) in thalamic stroke patients is still not well characterized, and this topic may open new avenues for future research.…”
Section: The Thalamus and Sleepmentioning
confidence: 99%
“…Moreover, patients with thalamic stroke may exhibit the symptoms of excessive daytime sleepiness [117]. Specifically, an Epworth Sleepiness Scale score in thalamic stroke patients was reported as a mean of 8-9 points, compared to 5-6 in the control group (extrathalamic and no-stroke) [49,51]. The stroke restricted to paramedian thalamus was described as being associated with severe arousal disturbances.…”
Section: Thalamic Stroke: a Model For Sleep-dependent Plasticity And ...mentioning
confidence: 99%
“…In a recent study we observed an association between a reduction of the slow-wave slope in patients with thalamic stroke and daytime sleepiness. 26 In addition, SWA is increasingly linked with sleep-related learning and memory, 27,28 processes that could play a role in neuroplasticity after stroke. 5 In support of this hypothesis, optogenetically induced slow waves delivered during sleep were reported to improve functional outcomes in a mouse model of stroke.…”
Section: Objective Assessmentsmentioning
confidence: 99%